IMPERIOUS RELATIONS IN THE STATES OF A TRADITIONAL SOCIETY: THE SOCIO-PHILOSOPHICAL ANALYSIS - Найчук, А. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
This article deals with the socio-philosophical analyses of the imperious relations in the states of a traditional society.